PENYADARAN GENERASI MUDA TERHADAP PERILAKU ANTIKORUPSI MELALUI PENDIDIKAN ANTIKORUPSI - Betari Anggi (Ganesha Civic Education Journal, 2022)
Education in fostering anti corruption behavior in 2016, based on the findings of a study of law students at Ganesha University's Faculty of Law. In a broader sense, it's about the importance of anti-corruption education in raising young people's level of legal literacy and empowering them to play a part in addressing the problem of corruption in Indonesia. This study employs an empirical strategy grounded in factual and conceptual approaches, and is presented in an analytical and descriptive format. As a result of this study, young people are better informed about corruption, its manifestations, and how to combat it. The only thing lacking is the information and will to combat corruption. This suggests that there is a generational gap in terms of young people's ability to recognize the need to foster an anti-corruption culture within themselves, leading to the inevitable conclusion be done.